The CURRENT TRENDS AND TREATMENTS IN DIABETIC RETINOPATHY - FIROZ MV; VISHAL GUPTA N; SANDEEP KANNA (Asian Journal of Pharmaceutical and Clinical Research, 2019)
The drastically increasing issues of the disease scenario currently are with different types of diabetes all over the world. It has been reported, approximately 592 million are suffering from the disease throughout the world. It affects differently in different patients with the disease. There have been reports that it is affected differently and also has different side effects. It is also been reported that diabetes mellitus leads to the cause of diabetic retinopathy (DR) and also diabetic macular edema. It is considered as one of the most common causes which is linked to DR. DR has been considered as one of the most important causes for the loss of vision or impaired vision. The drugs show different types of incompatibility such as toxicity, solubility issues, aggregation, and chemical degradation these can be improved by applying several methods. DR is classified according to “Airlie House” into different categories and based on different strategies and consideration. It was found that DR is the main cause for vision loss and also there no much strategies for development of new treatment. The treatment involved is laser photocoagulation and vitrectomy, among these the effective treatment, was found to be laser photocoagulation. This is mainly characterized as proliferative and non-proliferative DR. Different therapeutic agents have been taken for the study these includes vascular endothelial growth factor, renin-angiotensin system inhibitors and nonsteroidal anti-inflammatory drugs, they are certainly different interventions for the treatment, they are nanotechnology and liposome. Nanotechnology applied is the most effective and also acceptable way of treatment.